Calculation of Radiative Loss in Index Contrast of AlxGa1-xAs Waveguides - Ali, Latef M; Abed, Farah A (Al-Nahrain Journal of Science, 2013)
Abstract: In this paper we used a theoretical and numerical investigation model to calculate the radiation losses, penetration depth and effective indices for AlxGa1-xAs planar optical waveguides at a wavelength of 1550 nm. Newton-Raphson method was used to find the radiation modes and its wavenumber. It was found that the change in the refractive index of AlxGa1-xAs optical waveguide is responsible of scattering effects and radiation towards the substrate.